The Role of Clusters in the Economic Development of the North-West Regions of Russia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The purpose of this paper is to identify problems in innovation and show the role of clusters in the innovative development of the North-West regions of Russia. A characteristic feature of the present stage of economic development of the regions of the Russian Federation is the transition to an innovative socially oriented model of economic development based mainly on the generation, dissemination and use of knowledge. Analysis of policy documents on the federal, as well as macro-regional level regarding issues of strategy of innovative development has shown that the transition to an innovative model of development at the regional level is largely related to formation of clusters: High-tech clusters in urban areas; Clusters focused on the deep processing of raw materials and energy with the use of modern technologies in underdeveloped areas; Tourist and recreational clusters in areas with unique natural and climatic conditions; Transport and logistics clusters in areas with favorable geographical position. Great attention to the practical issues of creating clusters is also paid to the regional level. In the strategic development documents of the most of the subjects in the North-West of Russia specific clusters are identified, which could become locomotives of innovation development of the regional economy. The most common in the regions of North-West are the following clusters: forest, tourism, manufacturing, transport and logistics. Analysis of regional practices on creating clusters showed that they are mainly based on the existing specialization of regional economies. Insufficient attention is paid to identify and support of new innovative clusters, and formation of inter-regional clusters.